THE ROLE OF MOTIVATION IN STUDENT LEARNING AND ACADEMIC ACHIEVEMENT - Dilnoza Obidjonova, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This thesis explores the role of motivation in enhancing students’ learning processes and academic achievement. Motivation is a critical factor in education, influencing students’ engagement, persistence, and overall performance. Both intrinsic and extrinsic motivation are analyzed, with emphasis on their impact on learning outcomes. The study examines theoretical models of motivation, including self-determination theory and expectancy-value theory, and their application in classroom settings. Data were collected through surveys, interviews, and observational methods in secondary and higher education institutions. The findings indicate that highly motivated students demonstrate better academic performance, increased participation, and stronger self-regulation skills. Moreover, educators’ strategies to foster motivation, such as goal-setting, feedback, and collaborative activities, are highlighted as effective tools to enhance learning outcomes. The research also emphasizes the importance of creating supportive learning environments that nurture students’ interests and autonomy. This study provides valuable insights for teachers, curriculum designers, and policymakers seeking to implement evidence-based strategies to promote motivation and improve academic achievement.